2018
DOI: 10.1177/1077558718780592
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mental Health and Mental Health Care Disparities Research: 2011-2014

Abstract: Racial/ethnic minorities in the United States are more likely than Whites to have severe and persistent mental disorders and less likely to access mental health care. This comprehensive review evaluates studies of mental health and mental health care disparities funded by the National Institute of Mental Health (NIMH) to provide a benchmark for the 2015 NIMH revised strategic plan. A total of 615 articles were categorized into five pathways underlying mental health care and three pathways underlying mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 103 publications
(124 reference statements)
2
55
2
Order By: Relevance
“…discrepancies in caregiver-reported versus youth-reported mental health outcomes (e.g., Breland-Noble & Weller, 2012) and disparities in access to providers (e.g., Cook et al, 2019), the prevalence of mental health conditions may be underreported in this study, which, by extension, may indicate that the current findings do not accurately portray the relationship between mental health conditions and class membership. In sum, the current study provides instruction and an illustrative example of LCA.…”
Section: Discussion Of Examplementioning
confidence: 60%
See 1 more Smart Citation
“…discrepancies in caregiver-reported versus youth-reported mental health outcomes (e.g., Breland-Noble & Weller, 2012) and disparities in access to providers (e.g., Cook et al, 2019), the prevalence of mental health conditions may be underreported in this study, which, by extension, may indicate that the current findings do not accurately portray the relationship between mental health conditions and class membership. In sum, the current study provides instruction and an illustrative example of LCA.…”
Section: Discussion Of Examplementioning
confidence: 60%
“…Results need to be interpreted with caution because the presence of a current mental health condition was based on caregivers reporting whether a provider told them their adolescent had a mental health condition. Given potential racial biases in diagnostic practices as well as previous research consistently finding discrepancies in caregiver-reported versus youth-reported mental health outcomes (e.g., Breland-Noble & Weller, 2012) and disparities in access to providers (e.g., Cook et al, 2019), the prevalence of mental health conditions may be underreported in this study, which, by extension, may indicate that the current findings do not accurately portray the relationship between mental health conditions and class membership. In sum, the current study provides instruction and an illustrative example of LCA.…”
Section: Discussion Of Examplementioning
confidence: 66%
“…These conditions are all significant causes of morbidity and mortality in the US and are responsible for significant economic and societal burden. Among these diagnosis, significant health disparities exist including significant unmet need, poorer quality of care, and disparate healthcare utilization within these populations [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on Andersen's model of health services use, we consider that healthcare use results from the combination of a host of factors, including predisposing factors (in particular socio-demographic characteristics), enabling factors (such as an individual's living environment) and healthcare needs [20]. Based on previous literature, we also specifically define healthcare disparities as differences in access to and quality of healthcare which are not due to clinical appropriateness and patient needs [21].…”
Section: Conceptual Frameworkmentioning
confidence: 99%